Answer:
True
True
Explanation:
We are given that a series converges
We have to check that if series converges then the sequence of partial sum converges
Let
![\sum_(k=1)^(n)a_n=L](https://img.qammunity.org/2020/formulas/mathematics/college/gtwoezh52mh0oaai0ac1ti9dmw1xea3u71.png)
Because series converges
We have to show that
![\sum_(k=1)^(n-1)a_n=L](https://img.qammunity.org/2020/formulas/mathematics/college/f18uruhcfz98tw8igkezj47p9qe6og3wej.png)
When series converges then the nth term tends to zero.It is a sufficient condition .
Then
![\sum_(k=1)^(n)a_n=a_n+\sum_(k=1)^(n-1)a_n](https://img.qammunity.org/2020/formulas/mathematics/college/pewin4h8om0bm0ncd14qu6qu2wgzet6nym.png)
L=0+
![\sum_(k=1)^(n-1)a_n](https://img.qammunity.org/2020/formulas/mathematics/college/6jz5y922gdzy44uxyg37gr06nkel7ymqwg.png)
Hence,
![\sum_(k=1)^(n-1)a_n=L](https://img.qammunity.org/2020/formulas/mathematics/college/f18uruhcfz98tw8igkezj47p9qe6og3wej.png)
Therefore, if a series converges then the sequence of partial sum also converges is true.
If a series converges then the nth term tends to zero as n increases .It is a sufficient condition for series convergence .Hence, the statement is true.